Consumer Evaluations of Brand Imitations: An Investigation - Su, Sasa (Auckland University of Technology, 2006)
Brand imitation is viewed as an infringement of the imitated original brand. (Zaichkowsky, 1995). Although brand managers and researchers have looked into ways to fight against imitations, these are still prevalent in today's market. Researchers have found that one of the major reasons for the growing volume of imitations has been consumer demand. Thus, rather than studying ways to reduce imitations, it is first important for brand managers and researchers to understand why consumers would knowingly buy imitations. The major issue is to understand how consumers evaluate brand imitations. Several studies have explored factors that might have an influence on consumer evaluations of brand imitations. However these findings are limited. For example, similarity of the imitation to the original brand is an important factor in consumer evaluations. However, very little research has studied this aspect. Thus, this research is motivated to further investigate the influential factors of consumer evaluations of brand imitations. This study replicates d'Astous and Gargouri (2001), a study that examines a comprehensive set of factors that might influence consumer evaluations of brand imitations. The purpose of this study is to re-examine their hypotheses in various product categories, with a focus on luxury brands. Moreover, this study has extended the d'Astous and Gargouri (2001) study by investigating product similarity which had not been previously explored. However, hypothesis testing did not completely support the hypothesized effects. The results indicate that consumers who purchase luxury brand imitations are heavily influenced by the price and store image. The results show also that the factor of product similarity is unimportant to a customer purchasing imitator brands.
Keywords: Brand choice; Brand name products; Business